Linguistics Features of Reading Passage in English Text Book K-13 Revised Edition for Senior High School Students in Indonesia: Analysis of Basic Text Properties - Selvi Maryati; Safnil Arsyad; Syafryadin Syafryadin (English Education Study Program Faculty of Teacher Training and Education, 2021)
The objectives of this research are to identify the linguistic features contained in K 13 English textbook revised edition of grades X, XI, and XII published by the Ministry of Education and Culture of the Republic of Indonesia in terms of sentence pattern, types of tenses, voice, and aspect. This research is descriptive quantitative research. The sample of this research is thirty-nine reading passages were extracted from K13 English textbook revised edition published by the Indonesian Ministry of Education and Culture for senior high school students in Indonesia. All reading passages are taken as a sample, including fourteen texts of grade X, nine texts of grade XI, and sixteen texts of grade XII. The data were gathered by using a checklist and were analyzed by content analysis method. The findings showed that 1) The most common sentence patterns found are simple sentences. 2) Simple past tense is the majority of tenses used in reading the passages, especially at grade X and XI textbooks, while simple present tense is the dominant tenses found at grade XII. 3) The use of active voice dominates all reading passages at all grade levels. 4) The intensity of using the perfective aspect is higher than the imperfective aspect. 5) This result also implies that there are some differences in the findings of linguistic features from the three levels of this book. First, in terms of sentence patterns used in textbooks, at grade X the order of sentence patterns begins from the simple to the complicated one; simple sentences, then compound sentences, next complex sentences, and finally compound-complex sentences. Meanwhile, at grades XI and XII, the most complicated sentence patterns, namely compound-complex sentences, are less than compound sentences. Second, in terms of the types of tenses, the difference is that at grade X and XI textbooks, it is found that the dominant tenses used are simple past tense, while at grade XII textbooks, the most common tenses are simple present tense. these results indicate that the four linguistic features contained in English textbooks for high school In conclusion students in Indonesia need to be taught to students so that students can more easily understand and capture the meanings contained in the textbooks.